Risk Modeling of the Supply Chain for Thai Cassava Chip Exports to China - Suthep Nimsai; Thagoon Siriyod (International Journal of Supply Chain Management, 2019)
This study aims to review supply chain risks and construct a model of supply chain performance for Thai cassava chip exports to China to test the relationship between supply chain risks and supply chain performance. The primary theoretical model was constructed from four main supply chain risk factors, product risks, demand-side risks, logistical and infrastructural risks, and political risks, and five main supply chain performance variables, dependability, speed, qualities, information and response, adapted from [1] and S.M. [2]. Questionnaires were distributed to 46 Thai cassava chip exporters and stakeholders and analyzed using the PLS-SEM algorithm. With confidence intervals of 95%, demand-side risks and political risks impact supply chain performance. The Thai government and Thai entrepreneurs can analyze the results of possible risk factors to develop a supply chain for the Thai cassava chip industry.